2022
DOI: 10.3354/meps13910
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove carbon sustains artisanal fish and other estuarine consumers in a major mangrove area of the southern Caribbean Sea

Abstract: Estuaries are highly productive habitats that support fisheries production. However, the importance of mangrove carbon to estuarine consumers can differ considerably among systems. In this study, we used stable isotopes (δ13C, δ15N) to investigate the importance of mangrove carbon as an energy source to estuarine consumers in the Atrato River Delta, Colombia, an area where fringing mangroves dominate the coastline and where other productive coastal habitats that may otherwise support the food web are absent. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Multiple pathways of energy and nutrient flow exist in mangrove food webs due to the wide range of available food sources, such as plankton, benthic microalgae, mangroves, macroalgae, and macrophytes. 4 , 65 By assessing the trophic transfer of seabird-derived nutrients, we found that seabirds also enriched the mangrove invertebrate food web. We detected higher δ 15 N at seabird sites at all trophic levels, including baseline (sediments), primary producers (mangrove leaves), primary consumers (gastropods and sesarmid crabs), and a secondary consumer (portunid crab; Figure 4 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Multiple pathways of energy and nutrient flow exist in mangrove food webs due to the wide range of available food sources, such as plankton, benthic microalgae, mangroves, macroalgae, and macrophytes. 4 , 65 By assessing the trophic transfer of seabird-derived nutrients, we found that seabirds also enriched the mangrove invertebrate food web. We detected higher δ 15 N at seabird sites at all trophic levels, including baseline (sediments), primary producers (mangrove leaves), primary consumers (gastropods and sesarmid crabs), and a secondary consumer (portunid crab; Figure 4 ).…”
Section: Discussionmentioning
confidence: 92%
“…Nutrients can also be transferred to adjacent coastal habitats (such as coral reefs or seagrass areas) via mangrove leaf litter, which plays a key role in sustaining adjacent marine food webs. 65 Leaves with higher nutrient content or nutritive value are more rapidly broken down than less nutrient-rich leaves. 15 Seabird-derived nutrients from mangroves may therefore extend to adjacent marine communities through trophic pathways, for example via fish communities from nearby reefs or seagrass beds that utilize mangroves as nursery or feeding habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pathways of energy and nutrient flow exist in mangrove food webs due to the wide range of available food sources, such as plankton, benthic microalgae, mangroves, macroalgae and macrophytes 4,62 . By assessing the trophic transfer of seabird-derived nutrients, we found that seabirds also enriched the mangrove invertebrate food web.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate horizontal transfer of seabird-derived nutrients, from mangroves through tidally-mediated nutrient exchange. Nutrients can also be transferred to adjacent coastal habitats (such as coral reefs or seagrass areas) via mangrove leaf litter, which plays a key role in sustaining adjacent marine food webs 62 . Leaves with higher-nutrient content or nutritive value are more rapidly broken down than less nutrient-rich leaves 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove forests are unique tropical and subtropical ecosystems. They offer essential habitat and nursery grounds for commercially important fish and other fauna (Robertson & Duke 1987; Mohamed et al 2014; Huxham et al 2017), can sustain the secondary production of fisheries resources (Sandoval et al 2022), afford firewood, materials for the construction of houses and fishing gear and income (Djamaluddin 2004; Diele et al 2010; Chow 2018), protect coastlines from erosion (Lee et al 2014; Dasgupta et al 2019), bioremediate and help mitigate climate change by sequestering carbon (Murdiyarso et al 2015; Cameron et al 2019; Jennerjahn 2020). Despite their ecological and economic importance, mangroves have experienced significant degradation and deforestation (Polidoro et al 2010).…”
Section: Introductionmentioning
confidence: 99%